The plant community of a stretch of riparian vegetation in the upper Paraná River after 20 years of secondary succession (Batayporã, Mato Grosso do Sul, Brazil) - Luiz Antonio Frazatto Fernandes; Kazue Kawakita; Alexandrina Pujals; Victoria Sotti Batista; Mariza Barion Romagnolo (Acta Scientiarum: Biological Sciences, 2023)
The study of temporal changes in riparian vegetation is essential for understanding the paths taken by the ecosystem during ecological succession. In order to evaluate the changes in floristic composition, structure, and dynamics of the arboreal vegetation in an area of Semideciduous Seasonal Alluvial Forest, we aim to understand the secondary succession that occurs in the Paraná River floodplain. Based on a study conducted 20 years ago, in the municipality of Batayporã, Mato Grosso do Sul, a re-sampling was carried out in the same area, using the same methodology. Phytosociological and ecological parameters between the two temporal samplings were collected and compared using Student's ‘t’ test, where it was possible to find statistically significant variations (p<0.05) in the vegetation structure. A total of 603 individuals were sampled, distributed among 51 species and grouped in 46 genera and 31 families. The analysis of the distribution of abundance and importance values (IV) of species visualized in the histogram indicated an expected pattern in forest communities, which is the substitution of early successional species for late successional species. For the successional categories, the comparison of IVs revealed higher values for secondary species in both surveys and changes in the positions of climax and pioneer species, directly influencing the IVs values of these categories for the zones. When compared to the result obtained in the previous study, a replacement of the IV values of pioneer species with climax and dead species is noted. The comparisons showed that this phytocoenosis is evolving to a mature successional stage, a result of the decrease in the main anthropic impacts in the area. The results obtained highlight the importance of temporal monitoring of forest areas to expand the understanding of the pathways of ecological succession in this type of environment and provide information to assist in biodiversity conservation.